Fatigue life of concrete: Experimental study on the influence of loading conditions and material strength - Felix, Emerson Felipe; Carrazedo, Rogério; Possan, Edna (Revista ALCONPAT, 2022)
This work presents an experimental investigation aiming to evaluate the influence on the concrete fatigue behavior regarding the loading frequency, load intensity and the material’s compressive strength. Tests were carried out considering three loading frequencies (0.125, 0.25 and 0.5 Hz), two levels of maximum stress (50% and 70% of the compressive strength) and concretes made with three different compressive strength (30, 50 and 70 MPa). The results point out that as the loading frequency is increased, the fatigue life increases exponentially. However, it was observed that the fatigue life is shorter in high-strength concretes, i.e., the fatigue life presented an inverse relationship with the compressive strength.